A Study of Corrosion Patterns in Ancient Glass - Κορδαλή, Ουρανία (Πανεπιστήμιο Πελοποννήσου, 2017)
The corrosion mechanisms of ancient glasses is a complex process. The objects which have been exposed to the burial environments, usually lack of coherency and transparency. The examination of excavated corroded glasses, often concludes to alkalis loss and the formation of different corrosion patterns on the surface. In this study a collection of soda lime silica glasses is examined, aiming to the identification of the corrosion mechanism and its effects. The under study samples originated from the mainland Greece, Thebes. Since the composition of the examined samples have already determined this work is focusing to the different corrosion patterns which have formed. This research has a number of objectives: determination of the morphology of the surface of leached layer in glasses with different surface finishes, examination and correlation of the decay rate in different colored glasses, analysis of the concentration profiles of highly and slightly corroded samples and investigation of the burial environment based on the corrosion evidence. A combination of scientific analytical tools, such as SEM/EDS, LED-OM and RBS technique was used to completely characterize the corrosion mechanism. Destructive and non-destructive techniques were applied. The analytical data provided useful information about the decay rate and determined the corrosion patterns, occurred at the surfaces of the samples. Clear statements about the alkalis leaching and the surface homogeneity were resulted. Also, suggestions about the effects of different colorants at the deterioration process, have been stated.
Keywords: Γυαλί -- Ανάλυση; Γυαλί -- Επιφάνειες; Γυαλί -- Συντήρηση και αποκατάσταση; Υαλουργία -- Συντήρηση και αποκατάσταση; Χημική δομή; Αρχαιότητες; Γυαλί; Ανάλυση; Χημική σύσταση; Συντήρηση αρχαιοτήτων